Metalosato zinc in agronomic response and chemical composition of grass mombaza in ecuadorian amazon - Nivela Morante, Pedro Eduardo (2017)
This study aimed to improve the agronomic behavior of mombaza grass with supplemental fertilization of zinc metalosate, in order to raise the productive and nutritive parameters of the pasture. The investigation was carried out in the province of Orellana, canton Joya de los Sachas. A completely randomized design (DCA) with factorial arrangement 3 (zinc metalosate 0, 1, and 2 liters ha-1) x 3 (harvest age 28, 35 and 42 days) was applied. The variables studied were leaf weight (g), stem weight (g), number of leaves, leaf length (cm), stem leaf weight ratio (g), Biomass kg.ha-1, content of dry matter (%), protein (%), inorganic matter (%) and organic matter (%). At the 42 days of harvest, the highest results were obtained in leaf weight, stem weight, leaf number, leaf length, biomass and dry matter, but at 28 days of cut, stem, protein and organic matter. In effect interaction was highlighted 2 L ha-1 x 42 days cut in all agronomic variables, it was also evidenced that the interaction 2 L ha-1 x 28 days of cut achieved better effect on dry matter content with 30.12%, in addition to the protein content, the interaction between 1 L ha-1 x 28 days with 9.99% was highlighted and organic matter content stood out 0 L ha-1 x 28 days with 86.49%.